Peripheral absolute eosinophil count identifies the risk of serious immune-related adverse events in non-small cell lung cancer - Wu, Yan; Li, Dapeng; Wu, Mengyao; Yang, Ying; Shen, Meng; Chen, Kai (Frontiers in Oncology, 2022)
Background: Immune-related adverse events (irAEs) have drawn a lot of attention lately as a result of the predominance of immunotherapy in advanced non-small cell lung cancer (NSCLC). However, the clinical evidence for irAEs in real life is limited. In this paper, the occurrence of irAEs in Chinese NSCLC patients was examined, and possible risk factors for the emergence of severe irAEs were discovered. Methods: Our retrospective investigation assessed the occurrence of adverse events (AEs) and prognosis of 213 patients who received immunotherapy for NSCLC. Using univariate and multivariate logistic regression models, the association between clinicopathological traits and the incidence of severe irAEs was investigated. To assess the prognostic impact of irAEs, survival data was analyzed. Results: Among the 213 NSCLC patients, 122 (57.3%) had irAEs of any grade, and 38 (17.8%) had high-grade (grade 3-5) AEs. Baseline peripheral absolute eosinophil count (AEC) (HR 6.58, 95% CI: 1.5-28.8, P=0.012) was found to be an independent predictor of high-grade irAEs by multivariate analysis. The survival analysis revealed that patients with severe irAEs had worse OS (15.7 vs. 20.8 months, 95% CI: 11.6-19.8 vs. 16.0-25.5, P=0.026). Conclusion: According to our findings, the peripheral absolute eosinophil count (AEC) is a reliable indicator of severe irAEs in NSCLC. Serious irAEs that occur in patients often reflect poor prognoses. In the future, high-grade irAEs should receive more attention.